Obravnava bolnika s poklicno boleznijo - "poklicna anamneza" - Bilban, Marjan (Medicinski razgledi, 2009)
The objective of taking occupational history is for occupational medicine practitioners to find out about the relevant factors from the patient's work environment which may have a detrimental effect on humans and are known to have a causative association with various diseases.Extensive data on the used technological work processes and operations, harmful occupational factors, work conditions, the rhythm of work and work regimen, use of general and personal protective equipment, hygienic conditions at work etc. are essential for determining the diagnosis and proper treatment, as well as for selecting prophylactic activities. Data from a patient's occupational history that are related to potential occupational risks refer not only to the patient's current profession, but to all activities performed during his/her years of service (i. e. any potentiallate or delayed effects ofharmful occupational factors also ne ed to be taken into account). With respect to occupational diseases, the confirmation of dinical presentation, functional impairment and organ morphology also necessitate special procedures that are not us ed in thediagnosis of other, non-occupational diseases. The diagnosis always needs to be confirmed with a diagnostic method which can objectively verify health impairment (the degree ofwhich may also be expressed using a quantitative index). In some occupational diseases, the diagnostic procedure does not differ because of occupational causes (i. e. the impairment is verified in thesame way, irrespective of whether occupational or non-occupational factors are involved), while in others the diagnostic procedure is highly specific andis characteristic only of such diseases (e. g. confirmation of association between deviations of evaluation parameters and occupational exposure). (Abstract truncated at 2000 characters)
Keywords: Occupational Exposure; Rehabilitacija poklicna; Poklicna izpostavljenost; Occupational Diseases; Delovna sposobnost, ocenjevanje; Diagnosis; Disability Evaluation; Poklicne bolezni; rehabilitacija; Rehabilitation, Vocational; vocational rehabilitation; diagnostika